1994
DOI: 10.1002/1098-108x(199403)15:2<159::aid-eat2260150207>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Dieting, binge eating, and some of their correlates among secondary school girls

Abstract: A total of 440 girls from three private schools in Sydney completed a self‐report questionnaire that asked about their body‐ and weight‐related attitudes and practices, and assessed their reactions to the phenomenology of binge eating. The findings emphasize the integral relationship between dieting and disordered eating. Those who wanted to lose at least 7 kg, and were dieting most of the time, were more likely to be categorized as having a “severe” binge eating problem than were those who were happy with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 13 publications
2
21
0
1
Order By: Relevance
“…These findings support a large body of literature that has consistently found that weight loss is the most common body change strategy employed by female adolescents (Fox et al, 1994;Huon, 1994). However, the findings also demonstrate that male adolescents were more concerned with building muscle tone rather than weight loss and weight gain behaviors.…”
Section: Discussionsupporting
confidence: 85%
“…These findings support a large body of literature that has consistently found that weight loss is the most common body change strategy employed by female adolescents (Fox et al, 1994;Huon, 1994). However, the findings also demonstrate that male adolescents were more concerned with building muscle tone rather than weight loss and weight gain behaviors.…”
Section: Discussionsupporting
confidence: 85%
“…According to the literature, 70% of American women and 48% of Spanish women would like to be thinner, 19 and 50% of Australian women would like to weigh 7 kg less. 20 National studies on the topic have shown that 28.1% of Brazilian medical students feel fat even when they are normal weight 10 ; in addition, two thirds of the population assessed in Pelotas (RS) either would like to weigh less or feel fat, when in fact only one third of 18 -Rev Psiquiatr Rio Gd Sul. 2011;33 (1) Eating disorders in health science students -PEREIRA ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, women who do not meet the ideal standards (discussed later) demonstrate a greater dissatisfaction with their bodies than women closer to the ideal. More dieting and body dissatisfaction were reported by girls furthest from the ideal fi gure, larger girls especially (Huon, 1994).…”
Section: Body Shapementioning
confidence: 99%